Soil Chemical Properties and Microbial Biomass Respond during Land Use Change. Issue 1 (1st February 2022) - Parwi; Muhammad; Dewanti, F D; Priyadashini, R
Abstract: In Ponorogo, East Java, Indonesia, pine-based agroforestry was mostly converted to sengon-based agroforestry before partly converted to monoculture. Land-use changes during the process affect soil properties. There is few information about the effects of land-use changes from pine-based agroforestry systems to sengon-based agroforestry systems and monocultures on soil chemical properties and microbial biomass. The aims of this study were to analyze the response of soil chemical properties and microbial biomass to land use changes in latosol Indonesian. Samples from three land-use changes, i.e. pine-based agroforestry, sengon-based agroforestry and monoculture were analyzed. Soil samples were taken at 2 depths, i. e. 0-30 cm and 30-60 cm. As the results, it was found that the land-use change affected the chemical properties and microbial biomass of the soil. Land-used change from pine-based agroforestry to sengon-based agroforestry have no significant effect on pH, organic carbon, available P, and microbial biomass in 0-30 cm depth. Meanwhile, in 30-60 cmdepth, microbial biomass in sengon-based agroforetry was higher than that in pine-based agroforestry. The pine-based agroforestry which was converted into monoculture, reduced the soil organic carbon and available P concentration, contrast with the soil microbial biomass which was increased in 0-30 cm depth. The highest soil microbial biomass was found in sengon-based agroforestry in 30-60 cm depth. The conclusion of this study implicated that land use in monoculture decreased soil fertility. Therefore, conversion of pine-based agroforestry to monoculture is full of risks.